ANALYSIS OF HOMICIDAL DEATHS IN DISTRICT DI KHAN: AN AUTOPSY STUDY - Humayun, Muhammad; Khan, Dilawar; Zaman, Fasee -uz-; Khan, Jahanzeb; Khan, Omair; Parveen, Zahida; Humayun, Wajid (Journal of Ayub Medical College Abbottabad, 2009)
Background: One of the oldest crimes in human civilization is homicide which started from murder of Abel by the hands of Cane. With the passage of time manner of homicide have been changing. Study of pattern of homicide in any civil society is the first step towards development of intervention to reduce the impact of homicidal crimes. This study was conducted at the department of forensic medicine and toxicology Gomal Medical College DI Khan to know the pattern of the homicides, taking it as the first step in the prevention of crime. Methods: The present study was conducted over two years 2007-08. The data collected includes all reported unnatural deaths from the urban and rural areas of district on which autopsies were conducted in the district headquarter teaching hospital DI Khan and department of Forensic Medicine and Toxicology, Gomal Medical College DI Khan. Results: Homicidal deaths constituted 259/341 (76%) of all autopsies. Out of these homicides 59.07% were caused by the firearm. The most common firearm weapons were high velocity rifled weapons (AK-47, rifles and pistols). A total of 304 injuries were found in various body regions giving an average of about two injuries per victim/person. The head, neck and face sustained the highest numbers of injuries 100, (32.90%) followed by chest 91 (29.93%) and abdomen 47 (15.4%); the extremities, buttock and genitalia together sustained 65 (21.38 %) injuries. A part from firearm injuries unfortunately in our this study the second highest cause of homicidal deaths was bomb blasts injuries either due to suicide bombers or remote control bombs. The numbers of deaths due to blast injuries were 82 for the year 2007/08 out of total homicidal deaths and percentage was 32.66%. Conclusion: The vast majority of homicidal deaths in this area are caused by firearms like other big cities of the province like Peshawar, which bring up issues related to possession of firearms and change in cultural attitude towards the use of firearm, if a decrease in firearm related homicides is desired. Keywords: Firearm, unnatural deaths, autopsies, suicide bombing